Ionizacija snovi s svetlobo in primeri uporabe v biomedicini - Kamšek, Ana Rebeka (Matrika, 2019)
In this article the ionization of matter with visible and near-infrared light is discussed. The description of the process itself and the explanation of the relevant expressions are followed by descriptions of a few successful examples of application in biomedicine, such as the laser microtome, subcell surgery and assisted hatching in assisted reproduction.
Keywords: biomedicina; biomedicine; laserji; lasers; optics; optika